El sector productivo en la parroquia de flores y su aporte al emprendimiento empresarial del cantón Riobamba durante el periodo 2015-2016. - Gusñay Ilvis, Alberto (2017)
The present research is about The Production Sector in the Flores Parish and its support to entrepreneurship innovativeness of Riobamba Canton during the period 2015-2016, it was carried out with the objective of identifying the type of production that is given in the Flores Parish and it has focused on business entrepreneurship in Riobamba Canton. It was a quantitative research because it has been considered the amount of production and goods grown in the area. Strategies and action plans have been developed for the producers of the Flores Parish. Through a preliminary diagnostic in this parish, it has seen the Agricultural productions and channels of distribution to sell the products, for this reason it was done an external and internal analysis to apply the strategies and plans of action of this investigation. In order to obtain the results of the research project, the survey was applied to the producers of the Flores Parish, whose objective was to identify the agricultural production of this place and its impact on entrepreneurship in the Riobamba Canton. This investigation is of field as the source for defining strategies and action plans. In addition basic information was collected through primary and secondary sources and direct observation. As a conclusion, it is recommended to apply the strategies and plans of action in the Flores Parish to improve the agricultural production and distribution and to generate profits that allow them to improve their quality of life to the producers of the sector under study.